26‐1: Invited Paper: Thermally Activated Delayed Fluorescence Organic Light‐Emitting Diodes Comprising Ultrastable Glass Layers. Issue 1 (29th May 2019) - Will, Paul-Anton; Lenk, Simone; Reineke, Sebastian
Abstract : In our previous work, we investigated the effects of the formation of ultrastable glasses within monochrome phosphorescent organic light‐emitting diodes. 1 The ultrastable glasses are fabricated by heating the glass substrate to about 85% of the glass transition temperature while evaporation of the material. We observed significant enhancements of the external quantum efficiency (in the range of 20%) and device lifetime (up to 4x). These improvements are attributed to a denser packaging of the organic molecules resulting in reduced non‐radiative rates of the emitters. The change in the nano‐morphology can also have impact on the charge transport, the radiative rates of the emitter, and emitter orientation. For those properties, we have not identified a significant impact on the device performance. In this paper, we apply our concept to a green thermally activated delayed fluorescent emitter in a proof of principle device series. We find that insufficient energy transfer to the emitter holds back our devices from achieving state‐of‐the‐art efficiencies.